PENGARUH PEMBERIAN SENAM JANTUNG TERHADAP TEKANAN DARAH PADA LANJUT USIA (LANSIA) DENGAN HIPERTENSI DI PUSKESMAS SIMPANG IV SIPIN KOTA JAMBI - Mutmainah, Elya Siti; Yusnilawati, Yusnilawati; Anita Sari, Lisa; Oktarina, Yosi; Nurhusna, Nurhusna (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
Hypertension is a common non-communicable disease among the elderly. One non-pharmacological intervention to control hypertension is healthy cardiac exercise. This study aimed to determine the effect of healthy cardiac exercise on blood pressure in elderly patients with hypertension. A quasi-experimental pretest–posttest control group design was used with 48 respondents divided into intervention and control groups. The intervention group received healthy cardiac exercise three times per week. Blood pressure was measured before and after the intervention. The results showed a decrease in systolic blood pressure from 147.38 mmHg to 136.54 mmHg and diastolic blood pressure from 87.63 mmHg to 81.08 mmHg in the intervention group. Statistical analysis indicated a significant difference in blood pressure reduction between the two groups (p < 0.05). These findings indicate that healthy cardiac exercise has a significant effect on reducing blood pressure in elderly patients with hypertension